Mechanical Analysis Loads of Prosthetic Ankle Foot and Most Angle Effect during Walking Movement - Ali, Huda Falih Mahdi Mohammed; Jasem, Mays Hussein Ali; Masrahed, Safa Masrahed Mohammed; Abdelhamid, Ghada Ahmed Hussein (American Journal of Botany and Bioengineering, 2024)
A prosthesis is a device designed to replace a missing part of the body or to make a part of the bodywork better. Diseased or missing, arms, hands, legs, or prosthetic devices commonly replace joints. The computational prediction method is one of the fundamental steps in manufacturing medical devices. The prosthetic models were drawn using SOLIDWORKS 2016. The prosthetic mechanical load’s performance at different walking angles of mechanical was analyzed using numerical software called ANSYS 19. The results were statically analyzed by applying multi-criteria decision- making (MCDM). The analysis showed that for a vertical load of 120 N there was a maximum stress observed of 62.89 MPa at the first angle of heel-strike which is 19.81°. The mid-section of the foot where the three sections meet. The maximum weightage of mechanical loading modes criteria was observed for H1 by 0.33, followed T1 with 0.35. The lowest values have been taken for H4, and H3. The best angle performance was observed under mechanical load modes via applying the VIKOR method with AHP weights for each criterion in angle H4 (3.44 °) followed by H3 and, T3 for models. Then, the fourth angle was taken for T2 for. The sequence was followed for each of H2, T1 and H1.